2021
DOI: 10.1111/bjet.13131
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic versus teacher‐led sequencing in a digital serious game and the development of second language reading fluency and accuracy

Abstract: Recent years have seen a surge of calls for personalization of education. Automatised adaptivity in serious games has been advocated as a potential instantiation of such calls. Yet little is known about the extent to which personalised learning through automatised adaptivity poses an advantage for language learning over generalised teacher‐led sequencing in digital, game‐based learning environments. The goal of this paper is to address this question by comparing the learning outcomes in reading accuracy and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…We found that playing the game can enhance the knowledge of users regarding didactic materials on natural sciences, the acquisition of second languages, economics and business entrepreneurship, and mathematical concepts, as has already been examined in previous studies in relation to other games focused on education [37,41,43,44,47]. Playing this video game can also contribute to reading comprehension [47] and help change behaviour in relation to climate change [49].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We found that playing the game can enhance the knowledge of users regarding didactic materials on natural sciences, the acquisition of second languages, economics and business entrepreneurship, and mathematical concepts, as has already been examined in previous studies in relation to other games focused on education [37,41,43,44,47]. Playing this video game can also contribute to reading comprehension [47] and help change behaviour in relation to climate change [49].…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, these products can improve players' skills. Research shows evidence of improvements in the skills of health care professionals [45], social skills in companies [46], and reading comprehension skills [47]. There is also research showing that video games are a tool that can contribute to behavioural changes or to raising awareness of certain issues that affect society.…”
Section: Learning Achievements Through Video Gamesmentioning
confidence: 99%
“…The most frequently reported benefits were enhancing four language skills, communicative skills, perceptions and learning attitudes. It could be well documented that GBLL could not only facilitate K‐12 students' listening (Hwang et al, 2017), speaking (e.g., Khodabandeh, 2023; Wu et al, 2014), reading (e.g., Hooshyar et al, 2017; Serra & Gilabert, 2021), writing (e.g., Allen et al, 2014; Chang et al, 2021), grammar (e.g., Chu et al, 2019; Kasprowicz et al, 2019), and vocabulary (e.g., Chen et al, 2021; Elaish et al, 2019); but also support instant feedback and collaborative learning (e.g., Lawrence & Sherry, 2021; Wen, 2021), improve K‐12 students' attention span (e.g., Yu & Tsuei, 2022), decrease their negative emotions, e.g., anxiety, high cognitive load and fear of failure (e.g., Hsu, 2019; Raffone, 2022; Yang et al, 2021), and provide authentic learning contexts (e.g., Dalton & Devitt, 2016; Lan, 2015), among others. Various challenges should be cautioned as well, such as technical issues, difficult learning tasks, high cognitive load and anxiety, and difficulty in integrating GBLL into K‐12 curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Different taxonomies (Bernacki et al, 2021;Plass & Pawar, 2020) showed the large diversity among technology-mediated personalised learning environments. For example, it is not yet clear whether the sequencing of tasks is more effective when relying on algorithms which automatically decide on the sequencing of tasks than when teachers can change the sequence of the tasks themselves based on their own estimation of a child's ability, which Serra et al (2021) investigated within the context of a digital serious game. Participants used the learning tool for 6 months, and the effects of the sequencing (by the teacher or system) were examined through pre and posttests in terms of children's performance.…”
Section: Methodsmentioning
confidence: 99%